Low‐intensity exercise therapy with high frequency improves physical function and mental and physical symptoms in patients with haematological malignancies undergoing chemotherapy. (12th October 2018) - Fukushima, Takuya; Nakano, Jiro; Ishii, Shun; Natsuzako, Ayumi; Sakamoto, Junya; Okita, Minoru
Abstract: This study aimed to investigate the effects of low‐intensity exercise therapy (LIET) on the physical and mental symptoms and functions in patients with haematological malignancies undergoing chemotherapy. Forty‐four patients hospitalised for chemotherapy performed LIET. The exercise intensity of LIET was defined as achieving <40% of the predicted maximum heart rate calculated using the Karvonen formula. LIET consisted of aerobic and resistance training, which was carried out on weekdays. The intervention was omitted in the case of poor general health status and strong patient refusal. Muscular and physical function, activities of daily living (ADLs), psychological distress and quality of life (QOL) were evaluated upon initiation of rehabilitation and at discharge. Participants were divided into high‐ and low‐frequency groups according to their LIET frequency. Two‐way repeated‐measures analysis of variance was used for statistical analysis. In the high‐frequency group, muscle function was maintained, while physical function, ADLs, psychological distress and QOL were significantly improved. However, in the low‐frequency group, muscle function of the lower limb was significantly reduced and no other improvement was observed. Low‐intensity exercise therapy could be a potential treatment strategy for patients with haematological malignancies undergoing chemotherapy who are unable to perform mid‐ or high‐intensity exercise.